PENGARUH FAKTOR EKONOMI, MODAL SOSIAL, DAN RELIGIUSITAS TERHADAP PENGEMBALIAN PEMBIAYAAN MURABAHAH - Saadah Yuliana (Jurnal Ekonomi Pembangunan, 2015)
This study aims to prove empirically and analyze the influence of economic factors, Social Capital, and Religiosity against Returns Murabahah the People's Bank Syariah Financing (SRB). The study was conducted using 235 respondents. In collecting the data, this study used a survey method, while the research questionnaire using semantic differential scale. The sampling technique used is a convenient sampling. Exogenous latent variables used in this study are factors Economic, Social Capital, Religiosity, whereas endogenous latent variables namely Returns Murabahah. The results showed that the factors of Economic, Social Capital, and Religiosity positive and significant impact on the Return of Murabahah. Religiosity moderate the influence of economic factors on Financing Returns, which appears as a moderating influence that strengthens the influence of (amplifying effect). Religiosity moderating influence on the Social Capital Financing Returns, but appears as a moderating influence that neutralize or weaken the influence (moderating effect). Keywords: Religiosity, Social Capital, amplifying effect, moderating effect